Bio-Baterai dari Kulit Pisang: Diseminasi olah Praktis pada Ibu PKK Dusun Kallimpo - Andi Nurannisa; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Sartika Sari Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Batteries are one of the secondary interests that are needed in everyday life. The increasing use of batteries causes a buildup of used batteries that have been thrown away so far. In fact, battery waste includes waste that is difficult to decompose and contains hazardous and toxic materials, so it requires special handling in dealing with it. One effort that can be done is to recycle used batteries through processing banana peel waste into an electrolyte paste to replace carbon in the battery. This processing is carried out through dissemination of practical processing to PKK Dusun Kallimpo, Palakka Village, Kahu District with the product in the form of Bio-Battery. The activity was carried out in three stages, namely socialization, training and monitoring. The end result of this service is an increase in the knowledge and skills of PKK Dusun Kallimpo partners in processing banana peels into Bio-Battery as seen from the positive partner preferences with a percentage of 98%.